Illuminated but not electrified: An assessment of the impact of Solar Home System on rural households in South Africa. (1st October 2015) - Azimoh, Chukwuma Leonard; Klintenberg, Patrik; Wallin, Fredrik; Karlsson, Björn
Highlights: Light from Solar Home System electricity has the most positive impacts on the households. User education is necessary for the sustainability of Solar Home System programs. Solar Home System development impact is uncertain in South Africa. South African Solar Home System program is unsustainable. Abstract: The introduction of the off-grid electrification program in South Africa using the Solar Home System (SHS) was a central component of the government policy aimed at bringing development to un-electrified households. An assessment of the performance of SHS in many countries provided little evidence to support the development impact of the system. The general perception is that the SHS program is wasting government funds and has no hope of achieving the set objectives. Previous scientific reports have concluded that SHS is the most viable technology for bringing about socio-economic development to rural households. Most of these conclusions have been based on one sided arguments and largely on anecdotal evidence. This study provides a pluralistic view of the subject from the perspective of the energy service companies (ESCOs) and the households using the equipment. The development impact of SHS is subjected to scientific analysis by investigating the economic and social dimensions of the program. Additionally, the sustainability of the South African SHS program is assessed by investigating the challenges facing the ESCOs and the households. The study reveals that illumination provided by SHS electricity has profound impact on the livelihoods of rural households. Due to the limited capacity of SHS for productive and thermal use, there are limited direct economic benefits to the households. The associated economic impact is peripheral to the secondary usage of SHS electricity. SHS has improved the productivity of small scale business owners who utilize the light from SHS to do business at night. Irregularities in payment of subsidy funds and energy bills, high operation cost, non-optimal use of SHS, grid encroachment, and lack of customer satisfaction contribute to make the business unsustainable for the ESCOs.